2012
DOI: 10.1038/npp.2012.22
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Cocaine Motor Sensitization and Self-Administration in Mice Overexpressing Cannabinoid CB2 Receptors

Abstract: The potential involvement of the cannabinoid CB₂ receptors (CB₂r) in the adaptive responses induced by cocaine was studied in transgenic mice overexpressing the CB₂r (CB₂xP) and in wild-type (WT) littermates. For this purpose, the acute and sensitized locomotor responses to cocaine, conditioned place preference, and cocaine intravenous self-administration were evaluated. In addition, we assessed whether CB₂r were localized in neurons and/or astrocytes, and whether they colocalized with dopamine D1 and D2 recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
98
1
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(119 citation statements)
references
References 63 publications
(64 reference statements)
14
98
1
3
Order By: Relevance
“…In contrast, microinjections of the same doses of JWH133 into a dorsal brain region adjacent to the VTA failed to alter cocaine self-administration, suggesting an effect produced by activation of CB 2 Rs in the VTA, not in adjacent structures. This is consistent with our previous findings that systemic or local administration of JWH133 into the nucleus accumbens inhibits cocaine self-administration (22), and that transgenic up-regulation of brain CB 2 Rs attenuates cocaine self-administration and cocaine-induced increased locomotion (19). The present findings are also congruent with recent reports that brain CB 2 Rs have important roles in other DArelated functions and/or CNS disorders (12,25,51,52).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In contrast, microinjections of the same doses of JWH133 into a dorsal brain region adjacent to the VTA failed to alter cocaine self-administration, suggesting an effect produced by activation of CB 2 Rs in the VTA, not in adjacent structures. This is consistent with our previous findings that systemic or local administration of JWH133 into the nucleus accumbens inhibits cocaine self-administration (22), and that transgenic up-regulation of brain CB 2 Rs attenuates cocaine self-administration and cocaine-induced increased locomotion (19). The present findings are also congruent with recent reports that brain CB 2 Rs have important roles in other DArelated functions and/or CNS disorders (12,25,51,52).…”
Section: Discussionsupporting
confidence: 93%
“…This finding is supported by recent studies demonstrating that systemic administration of the CB 2 R agonist O-1966 inhibited cocaine-induced conditioned place preference in WT mice, but not in CB 2 −/− mice (23), and that increased CB 2 R expression in mouse brain attenuates cocaine self-administration and cocaine-enhanced locomotion (19). In addition, brain CB 2 Rs may be involved in several DA-related CNS disorders, such as Parkinson's disease (24), schizophrenia (25), anxiety (26), and depression (27).…”
supporting
confidence: 70%
See 1 more Smart Citation
“…Previous studies suggest a relevant role of CB2r on opiates, cocaine, and ethanol addiction behavior (Adamczyk et al, 2012;Aracil-Fernandez et al, 2012;Onaivi et al, 2008b). To explore the role of CB2r in the rewarding properties of nicotine, CB2KO mice were exposed to the CPP following an unbiased procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed that activation of CB2r is involved in cocaine-induced reinstatement of cocaine-seeking behavior, although its activity is not necessary for the rewarding effects of cocaine (Adamczyk et al, 2012). In addition, latest results from our group suggest that overexpression of CB2r (CB2xP mice) decreases cocaine motor responses and cocaine self-administration (Aracil-Fernandez et al, 2012).…”
Section: Introductionmentioning
confidence: 86%